NON-GENETIC FACTORS AFFECTING LINEAR TYPE TRAITS IN SAHIWAL COWS - M. A. Khan; M.S. Khan (Journal of Animal and Plant Sciences, 2015)
The present study was designed to find out the magnitude of environmental factors affecting linear type traits in Sahiwal cattle. There were 790 observations for linear type traits on 310 lactating Sahiwal cows progeny of 53 sires. The linear model included fixed effects of herd, parity and stage of lactation at classification. The age of cow at classification was used as co-variable. The ASReml (Version 2.0) was the statistical package used (Gilmour et al. 2007). Herd, parity, stage of lactation and age at classification effects were significant for chest width, body depth, rear udder height, udder depth, rear udder width, thurl width, angularity and fore teat length (P<.001-.05). Herd, parity and stage of lactation effects were significant for stature, central ligament and dewlap surface area (P<.001-.05).  Herd and stage of lactation effect was significant for rear legs set and rump width (P<.001-.05). Herd and parity of cows affected linear type scores significantly (P<.001-.01). Herd, parity and age at classification effects were significant for rear legs rear view (P<.01-.05).
Keywords: Non-genetic factors; linear type traits; Sahiwal cows